Successful Use of Hyperbaric Oxygen as Adjunctive Therapy for a Nonhealing Venous Ulcer in a Patient with Systemic Sclerosis and Pulmonary Arterial Hypertension: A Case Report and Review of the Literature - Isaac Biney; Tina Dudney; Mitchell Goldman; Lee Carder; Elise Schriver (Case Reports in Pulmonology)
Skin ulcers are a common complication of systemic sclerosis (SSc) that can significantly impact the quality of life. There have been recent reports on the use of hyperbaric oxygen therapy (HBO2T) in the management of nonhealing systemic sclerosis skin ulcers. The effect of HBO2T on pulmonary arterial hypertension (PAH), another common and potentially life-threatening complication of SSc, is unclear with literature on the subject lacking. We present the case of a 65-year-old female with limited SSc complicated by severe PAH and a nonhealing left lower extremity venous ulcer. HBO2T was successfully used as an adjunct in her management resulting in complete resolution of the venous ulcer and improved quality of life without any adverse effects on her pulmonary arterial hypertension.